Impact of Feed Mixture on Kinetic Strength of Pellets for Poultry (Agricultural Engineering, 2017)
The paper presents the impact of feed mixtures for poultry on their kinetic strength determined with Holmen's method. Research material came from a production line and 9 pelleted feed mixtures for poultry with diameter of 3.2 mm were accepted for the research. Feed was prepared, pelleted and cooled with the use of the same devices and their exploitation settings were comparable with regard to the investigated feed pellet. The obtained research results proved that kinetic strength of the investigated feed pellets was statistically significant in relation to the composition of the feed mixture. Relations of kinetic strength of pellets to the composition of the feed mixtures were determined with the multiple regression method. From the determined models the highest utilitarian value may occur in case of a model with four explanatory variables: corn (x1), wheat (x2), soya meal (x4) and fat (x5).